Management of Medicines and Health Supplies Hospitals in Indonesia - Silfia Septiani; Aisyah Putri Solin; Saski Amalia Khairunnisa; Aindah Safitri Dinata; Sri Wahyuni Siregar; Dewi Agustina (Universitas Ibn Khaldun Bogor, 2023)
Drug management is a collection of activities carried out optimally related to the planning, procurement, storage, distribution, and destruction of drugs to ensure the correct number and types of care and treatment supplies. This is done to meet the needs of humans who require primary care. The research objective is to ensure that the use of funds is optimized by increasing the effectiveness and efficiency of drug management through increasing suitability, equality, and availability of diverse and appropriate drug supplies for access. Research Method using the literature study or literature review method by scanning the Google Scholar database with the terms